Optometry Australia's chairside reference for the diagnosis and management of age‐related macular degeneration. (30th September 2019) - Hart, Kerryn M; Abbott, Carla; Ly, Angelica; Kalff, Susan; Lek, Jia Jia; Milston, Rebecca; Page, Gary; Robertson, Bill; Ayton, Lauren
Abstract : Age‐related macular degeneration (AMD) is the leading cause of irreversible vision loss in people over the age of 50 years in Australia. Optometry Australia has developed this AMD chairside reference in consultation with a member‐based working group comprised of experienced practitioners. It provides an evidence‐based approach to current best practice in the diagnosis and management of AMD. Optometrists should be competent in assessing patients with or at risk of developing AMD, so that they are able to provide evidence‐based management including appropriate communication, diagnosis and referral when indicated. This AMD chairside reference covers risk factors for the development of AMD or progression to late‐stage AMD; the current clinical classification of AMD; common signs and symptoms; optometric assessment including ocular imaging and biomarkers; differential diagnoses; and management of early, intermediate and late AMD. Optometry Australia's chairside reference is intended as a general guide for optometrists, and is not a formal management protocol.